Mighty Max - Weston, Carrie; Bradford, Tim (London, England, UK : Bloomsbury Education, 2018)
Max is a monster with yellow eyes, pointed ears, a big, wide mouth, sharp teeth and a long, spiky tail. He's just like the rest of his family, except Max is a mighty show off. He's not really meant to, but sometimes he does tricks in front of the children who visit Blue Lake - and they love it! Then, one day, his showing off gets Max more than he bargained for ...
Originally published: A & C Black, 2009.
"Gold Book Band" back cover.
GS
Text in English
Keywords: Monsters -- Juvenile fiction; Friendship -- Juvenile fiction; Readers (Elementary).; Children's stories